Espectro de emisión de un sistema de cavidades acopladas con un punto cuántico (2013)
ABSTRACT: Recently, the strong coupling regime between matter excitations in a Quantum Dot (QD) and a light mode confined in a Photonic Crystal Cavity (PhC-C) was achieved. This opens up the possibility to Cavity Quantum Electrodynamic (CQED) physics in solid state systems. In this contribution, the emission spectrum of a QD confined in a PhC-C and near to a second empty cavity is calculated using a master equation that includes Lindblad decoherence and pumping terms. The theoretically derived spectrum is compared with experimental results.